Formulasi sediaan lotion poliherbal minyak alpukat (Persea americana) dan ekstrak seledri (Apium graveolens L) sebagai pelembab kulit - Bylla, Salsa; Salman, Salman; Sari, Nurmala; Sihotang, Supran Hidayat; Indriana, Meutia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: avocado oil contains vitamins A, D, E and lecithin. This content is efficacious to moisturise and regenerate the skin, and it is a natural sunscreen that protects the skin from UV rays. The flavonoid content in celery can neutralise free radicals and prevent premature aging. Then, this plant can be processed and used as a cosmetic preparation in the form of lotion. Polyherbs are cosmetic products that contain one or more herbal substances. This study aimed to determine whether avocado oil (Apium graveolens L) and celery (Persea americana) in polyherbal lotion preparation extracts can provide skin moisture. Methods: the method used is experimental by making celery extraction by maceration using 96% ethanol solvent and concentrated with a rotary evaporator and avocado oil as a combination lotion preparation of 1.5%, 2%, 2.5% and 3% concentrations. As blanks used lotion base. Tests on lotion preparations include homogeneity tests, pH measurements, determination of emulsion type, stability, irritation to volunteers, liking/hedonics, moisture effectiveness compared with existing preparations, using the Skin Analyzer Detector tool, and antioxidant activity tests. Result: the results of the study showed that all lotion preparations were homogeneous, had a pH of 6.2-5.9, emulsion type M/A and were stable during storage of 4 weeks. Lotion preparations of avocado oil and celery extract with a concentration of 3% can provide the best moisturising effect on the skin after 4 weeks. All polyherbal lotion preparations of avocado oil and celery extract do not irritate the skin; celery ethanol extract and avocado oil have antioxidant activity in the